FORMULASI KRIM TABIR SURYA EKSTRAK KULIT NANAS (ANANAS COMOSUS L MERR) DAN UJI IN VITRO NILAI SUN PROTECTING FACTOR (SPF) - Damogalad, Viondy; Edy, Hosea Jaya; Supriati, Hamidah Sri (PHARMACON, 2013)
This research aims to determine the value of sun protecting factor (SPF) of pineapple skinextracts (Ananas comosus L Merr) in the form of cream with variant concentration of 2%,4% and 8%. The pineapple skin contains flavonoids and tannins substances that can give theeffect as a sunscreen. The formulation of pineapple skin extract cream using the phase of oilin water. The ingredients that was use in the cream formulation are stearic acid, liquidparaffin cera alba, cetyl alcohol, stearyl alcohol, propylene glycol, triethanolamine, distilledwater and nipagin. Cream of pineapple skin extract then giving a variety of specified qualitytesting and SPF value. Each concentration cream diluted using 96% ethanol. Creams that hasbeen diluted read it’s absorbance value at UV-Vis Spectrophotometer instrument thencalculated the SPF values. The results showed that the cream of pineapple skin extract hasmet the requirements after conducting various quality of cream tests and the SPF value ofeach cream concentrations are very low. It’s been Concluded that the concentration ofpineapple skin extract cream 2% has shown a very small SPF value and increasing theconcentration of 4% and 8% demonstrate higher SPF values but still does not meet thestandards as a good sunscreen cream.Keywords : cream, extract, pineapple skin, sunscreen, sun protecting factor